Changes of Sand Fly Populations and Leishmania infantum Infection Rates in an Irrigated Village Located in Arid Central Tunisia - Barhoumi, W.; Fares, W.; Cherni, S.; Derbali, M.; Dachraoui, K.; Chelbi, I.; Ramalho-Ortigao, Marcelo; Beier, J. C.; Zhioua, E. (My University, 2016)
The current spread of zoonotic visceral leishmaniasis (ZVL) throughout arid areas of Central Tunisia is a major public health concern. The main objective of this study is to investigate whether the development of irrigation in arid bio-geographical areas in Central Tunisia have led to the establishment of a stable cycle involving sand flies of the subgenus Larroussius and Leishmania infantum, and subsequently to the emergence of ZVL. Sand flies were collected from the village of Saddaguia, a highly irrigated zone located within an arid bio-geographical area of Central Tunisia by using modified Centers for Diseases Control (CDC) light traps. Morphological keys were used to identify sand flies. Collected sand flies were pooled with up to 30 specimens per pool according to date and tested by nested Polymerase Chain Reaction (PCR) DNA sequencing from positive pools was used to identify Leishmania spp. A total of 4915 sand flies (2422 females and 2493 males) were collected from Saddaguia in September and in October 2014. Morphological identification confirmed sand flies of the subgenus Larroussius to be predominant. PCR analysis followed by DNA sequencing indicated that 15 pools were infected with L. infantum yielding an overall infection rate of 0.6%. The majority of the infected pools were of sand fly species belonging to subgenus Larroussius. Intense irrigation applied to the arid bio-geographical areas in Central Tunisia is at the origin of the development of an environment capable of sustaining important populations of sand flies of the subgenus Larroussius. This has led to the establishment of stable transmission cycles of L. infantum and subsequently to the emergence of ZVL.
Citation: Barhoumi, W., Fares, W., Cherni, S., Derbali, M., Dachraoui, K., Chelbi, I., . . . Zhioua, E. (2016). Changes of Sand Fly Populations and Leishmania infantum Infection Rates in an Irrigated Village Located in Arid Central Tunisia. International Journal of Environmental Research and Public Health, 13(3), 10. doi:10.3390/ijerph13030329
Keywords: Sand Flies; Leishmania Infantum; Phlebotomus Perfiliewi; Emergence Of; Zvl; Phlebotomus Longicuspis